Secretion of circular proteins using sortase - Strijbis, Karin (Methods Mol Biol, 2014)
Circular proteins occur naturally and have been found in microorganisms, plants and eukaryotes where they are commonly involved in host defense. Properties of circular proteins include enhanced resistance to exoproteases, increased thermostability, longer life spans and increased activity. Using an enzymatic approach based on the bacterial sortase A (SrtA) transpeptidase, N- and C-termini of conventional linear proteins can be linked resulting in a circular protein. Circularization of bioengineered linear substrate proteins can indeed confer the desirable properties associated with circular proteins. Here we describe how cells can be manipulated to secrete circularized proteins for substrates of choice via sortase-mediated circularization in the lumen of the endoplasmic reticulum.